Barriers and potential facilitators to the implementation of government policies on front-of-pack food labeling and restriction of unhealthy food advertising in Thailand. (August 2017) - Phulkerd, Sirinya; Sacks, Gary; Vandevijvere, Stefanie; Worsley, Anthony; Lawrence, Mark
Highlights: Successful implementation requires attention towards building and strengthening organizational capacities. Infrastructure aspects have great potential for impact on other factors to support or hinder the implementation. Concerted efforts are important for overcoming the implementation barriers. Abstract: Thailand is experiencing an increasing burden of obesity and diet-related non-communicable diseases. The Thai government has responded by developing a number of policies to protect and promote healthy eating. In particular, in 2008, the Thai Government passed a regulation to restrict unhealthy radio and television food advertising to children (RTA). In the following year, a voluntary front-of-pack nutrition labeling policy to promote those products that had reduced their sugar, fat and/or sodium content by at least 25% (25% SFS) was passed. However, the extent of implementation of both of these policies has been poor to date. The aim of this study was to identify barriers and potential facilitators to the implementation of both the RTA and 25% SFS policies. Semi-structured interviews were conducted with 28 participants holding senior positions in government, industry and civil society organizations closely involved in the implementation of these policies. The interview data were analyzed using the thematic framework analysis approach. The major barriers to policy implementation perceived by participants were a lack of a monitoring and evaluation system, a lack of organization knowledge regarding skills required for implementation, poor governance system, lack of funding and resources, lack of effective multi-sectoral platforms, influence of the food industry, lack of clear policy content, organizational culture and structure, and changes in policy priorities. Factors that potentially facilitated implementation of these policies, as identified by participants, were policy being compatible to implementer's context, individual support from government officials, good financial management mechanisms, inter-organization networks, and personal motivation to implementing policy. The successful implementation of policies to create healthy food environments in Thailand will likely require attention towards improving the capacity and authority of government agencies, infrastructure to support multi-sectoral platforms and inter-organizational networks, and adequate resources.